Sex Education in Early Childhood: Learning Materials for Young Children’s Sexual Development - Zhilla Rahim (Inovan Publisher, 2025)
Sexual education should be considered an essential subject in early childhood education. Providing appropriate materials can serve as a preventive measure against immoral acts, particularly sexual violence, which often occurs due to children’s lack of understanding about behaviors that may lead to sexual misconduct. This study aims to explain the sexual education materials that can be taught both at school and at home. The research method employed is a literature review. Based on the analysis of eleven studies, several sexual education materials were identified as effective in enhancing children’s knowledge and protecting them from sexual violence. These materials include: (1) introduction to body parts and their functions, (2) gender identity, and (3) self-protection